First report of Epistylis unioi Gong 1986 (Sessilida: Epistylididae) infecting fry of Pelteobagrus fulvidraco in Hubei, China - Li, Ming; Li, Weidong; Ge, Xianping; Wang, Chong; Zhang, Lin; Huang, Feng; Liu, Huiyu (Zootaxa, 2012)
The peritrich Epistylis unioi Gong, 1986 was collected from fry of Pelteobagrus fulvidraco during parasite surveys at Hon-ghu Lake Fish Hatchery, Hubei Province, central China in May 2010 and redescribed. Some revisions were done basedon live, silver-impregnated, and SEM specimens. The zooid is elongated and somewhat vase-like in shape, measuring56–88 × 22–38 µm in vivo. A single contractile vacuole is apically located slightly below the peristome disc. The macro-nucleus is horseshoe-shaped, always transversely situated at the foreside of the body. Haplokinety (H) and polykinety (Po)complete one and one-half circuits on the peristome before entering the infundibulum, with a distal kinetal fragment pres-ent at the distal end. Silverline system consists of 37–45 pellicular striations between peristome and aboral trochal band(TB), and of 26–33 between TB and scopula. Colony is asymmetrically and dichotomously branched, usually with onlytwo levels of branches. In addition, the telotrochs of E. unioi were also observed and its structures were described herein.Besides, obvious skin lesions caused by the ringlike base of E. unioi were detected and the relationship between these epizooites and their hosts was briefly discussed as well.